Penerapan Metode Syawir untuk Mengembangkan Pemahaman Materi Fiqih Santri di Pondok Pesantren Bani Alawiyah Probolinggo - Wahyuni, Siti; Nuha, Nazahah Ulin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study aims to examine the application of the Syawir method in a pesantren institution among the students (santri). The students at Bani Alawiyah Islamic Boarding School are highly enthusiastic about mastering the study of fiqh, which sparked the researcher’s interest in further investigating the method used in fiqh learning. This research is a field study, specifically descriptive qualitative research, designed to describe the implementation of the Syawir method in fiqh learning using the *Fathul Qorib* book at Bani Alawiyah Islamic Boarding School. Data was collected through observation, interviews, and documentation. The research informants consisted of the head, administrators, class supervisors, teachers, and students. The results of the study indicate that the students at Bani Alawiyah Islamic Boarding School in Probolinggo have applied the Syawir method in learning fiqh from the *Fathul Qorib* book. This method has improved the students' understanding of the fiqh material, which they initially struggled with. The method not only enhances their comprehension of the material but also fosters their social and critical thinking skills, helping them to solve complex problems. This method is implemented to achieve the goal of engaging in effective discussions (musyawarah) before progressing to the next level.